The neuropathology of the social cognitive network in autism - McKavanagh, R (2014)
Potential differences in developmental trajectory were investigated in autism at both the macro- and micro-scopic scale, using regional volumetric measurements from in-vivo scans and measurements of minicolumnar organisation of the cortex in post-mortem tissue. In addition, a study was carried out to investigate the sensitivity of measures of cortical diffusion to cortical architecture. Three key regions of interest were studied throughout this thesis, orbital frontal cortex (BA11), primary auditory cortex (BA41) and part of the inferior parietal lobe (BA40). Subjects with ASD showed increases in grey matter in left parietal cortex and decreases in left BA11 compared to controls. In addition, subjects with ASD showed increased grey matter volume with age in both BA41 and the inferior parietal lobe, whereas controls only showed a negative correlation between grey matter volume in BA41 and age. Wider minicolumns were found in ASD in all regions, suggesting pathology is not restricted to higher order association areas. Differences seemed more pronounced at younger ages suggesting an altered developmental trajectory in ASD. Such an increase in minicolumnar width arguably underlies the feature-based processing style seen in ASD. A pilot study using post-mortem DTI scans of MS brains revealed a relationship between measures of the directionality of diffusion and the width of axonal bundles in the cortex, an aspect of the minicolumnar arrangement. When extending this investigation to a set of ASD and control brains, evidence was found for different relationships between axon bundle width and measures of the directionality of diffusion in the cortex, suggesting that although differences in axon bundle width were not seen between groups, there may be differences in the composition of the axon bundles between ASD and control groups.